Penggunaan Metode Discovery Learning untuk Meningkatkan Hasil Belajar Siswa Kelas V dalam Mata Pelajaran Pendidikan Pancasila di Sekolah Dasar - Devi Dwi Oktavia; Tabroni Tabroni (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research aims to improve the learning outcomes of Natural and Social Sciences (IPAS) by applying a discovery learning model assisted by image media in grade V of SD Nurul Khoir, Jambi City. The method used is Class Action Research (PTK) which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementation of actions, observation, and reflection. The research subjects amounted to 26 students. Data collection techniques are carried out through learning outcome tests, observation of teacher and student activities, and documentation. The results of the study showed a significant increase in the completeness of student learning outcomes. In cycle I, completeness reached 73.92%, and increased to 85.30% in cycle II. This improvement shows that the application of the discovery learning model combined with image media is effective in improving IPAS learning outcomes. This model encourages active involvement of students in the learning process, fosters curiosity, and hones critical and logical thinking skills. Image media as a visual aid has also been proven to be able to strengthen concept understanding and improve students' memory of the material studied. In addition, the learning process becomes more fun and meaningful because students are directly involved in the activity of discovering concepts through the stages of observing, questioning, gathering information, reasoning, and concluding. Teachers are no longer the center of information, but play the role of learning facilitators. This strategy is also relevant to the cognitive development characteristics of elementary school students who tend to favor concrete and visual learning. Thus, the application of the discovery learning model assisted by image media can be an alternative to an effective and innovative learning strategy in improving social studies learning outcomes. Teachers are advised to continue to develop adaptive, creative, and contextual learning methods and media.